Pengaruh Budaya Organisasi dan Kompetensi Sumber Daya Manusia terhadap Kinerja Anggota Organisasi pada Unit Kegiatan Mahasiswa Universitas Bangka Belitung - Resvita Aprilianti; Wirena Nayala; Tasya Armenda; Indah Noviyanti (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to examine and analyze how organizational culture and human resource competencies influence the performance of members in Student Activity Units (UKM) at the University of Bangka Belitung. The main problems identified include low commitment, active participation, and member competencies, which impact the effectiveness and sustainability of the organization. This study employs a quantitative approach as a survey method involving all UKM members as respondents, totaling 123 individuals, using a saturated sampling technique. Data analysis was conducted using linear regression to identify relationships between variables. The results indicate that organizational culture and human resource competencies have a positive and significant influence on organizational member performance. Strengthening an inclusive and professional organizational culture, as well as enhancing member competencies through training and development, are recommended as key strategies to improve SME performance in the university environment. These findings are expected to serve as a reference for SME managers and university authorities in formulating sustainable policies for student organization development